Renewable Insulation Materials Constructed from Colombian Materials According to the Principles of Sustainable Development: a Review - Herrera Martínez, Marcelo; Páez Soto, Darío Alfonso (TECCIENCIA, 2018)
The growing demand for building materials requires the development of environmentally friendly materials with excellent use properties and reasonable prices. One of the major objectives of materials research in the construction industry is the use of renewable resources from waste materials from industries for the development of new building materials. The current trend of thermal insulation of buildings has resulted in the development of materials for insulation based on renewable resources of agriculture. This article describes the research and development of insulation materials based on natural fibres of agricultural origin; in particular, guadua fibres, sugar cane, hemp, flax and jute.